PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK EIGER DI EIGER STORE UNIMED - INDRIANINGSIH ,; TOGU HARLEN LUMBAN RAJA; LASMAN EDDY BACHTIAR (LP2MTBM MAKARIOZ, 2022)
This study aims to analyze the effect of Brand Image and Product Quality on Eiger Product Purchase Decisions at Unimed's Eiger Store. The data collection method in this study used a questionnaire which was then processed using multiple linear regression analysis. The test used to test the research is a test of validity and reliability. Hypothesis test is by partial test (t) and stimulant test (f). The results of the analysis of this study resulted in Brand Image (X1) having a positive effect on Purchase Decisions (Y). With a value of tcount = 3.728 with a significance level of 0.001. While the variable Quality (X2) has a positive effect on Purchase Decisions (Y). With a value of tcount = 4.628 with a significance level of 0.000. The results of the analysis with the f test resulted that the Brand Image (X1) and Quality (X2) variables together had a positive effect on Purchase Decision (Y) with Fcount of 57.669.